The Moderating Effects of Ecological Workforce Management on the Association Among Aligned Variables in Ecological Performance in the Manufacturing Industry. - Suba, M.; Inayath Ahamed, S. B. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
green human resource management is a recent and most important topic in every organization. At present every individual is focusing on eco-friendly activities and products of every manufacturing organization. Due to some climate changes, like global warming and various types of pollution we are in the stage of taking care of the environment. As a consequence, most organizations are following some steps to reduce the negative impacts on nature. In this article, the researcher wants to examine the relationship among some measurements related to ecological personnel management in the textile industry. The researcher used SPSS for the representation. This article shows the relationship impacts transactional leadership, ecological contrivances, and observed managerial prop-ups to betterment the result of the environmental performance of the organization through ecological manpower management.